Climate impacts on air quality and child health and wellbeing: Implications for Oceania. (18th November 2021) - Sly, Peter D; Vilcins, Dwan
Abstract : Despite the enormous gains in reducing child mortality resulting from the United Nations Millennium Development Goals, in some ways children's future wellbeing has never been under greater threat. Climate and environmental change, primarily driven by poor air quality, represents a major threat to child health and wellbeing, through both direct and indirect effects. Climate change has multiple environmental consequences impacting negatively on child health and wellbeing, including increases in ambient temperature, rising atmospheric carbon dioxide (CO2), altered distribution of rainfall, ocean warming, rising sea level and more frequent and severe adverse weather events. Multiple pathways link these exposures to a wide variety of adverse health outcomes. Countries in Oceania are especially likely to be subjected to the effects of increases in ambient temperature, altered distribution of rainfall, ocean warming and sea level rise. These changes pose a significant risk to children and provide a moral imperative for us to act to protect child health.